2019
DOI: 10.3390/jcm8122053
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of AAV1-Rheb(S16H) Transduction Against Alzheimer’s Disease

Abstract: We recently reported that adeno-associated virus serotype 1-constitutively active Ras homolog enriched in brain [AAV1-Rheb(S16H)] transduction of hippocampal neurons could induce neuron-astroglia interactions in the rat hippocampus in vivo, resulting in neuroprotection. However, it remains uncertain whether AAV1-Rheb(S16H) transduction induces neurotrophic effects and preserves the cognitive memory in an animal model of Alzheimer’s disease (AD) with characteristic phenotypic features, such as β-amyloid (Aβ) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 48 publications
(81 reference statements)
0
18
0
Order By: Relevance
“…The activation of mTORC1 induced by Rheb(S16H) transduction of hippocampal neurons was found to result in BDNF production, which protected against thrombin-induced neurotoxicity in the rat hippocampus [5]. In the same manner, AAV1-Rheb(S16H) transduction in the hippocampus of transgenic AD mice prevented cognitive function impairment [26,29].…”
Section: Mutation Of Rheb Leading To Constitutive Activationmentioning
confidence: 90%
See 4 more Smart Citations
“…The activation of mTORC1 induced by Rheb(S16H) transduction of hippocampal neurons was found to result in BDNF production, which protected against thrombin-induced neurotoxicity in the rat hippocampus [5]. In the same manner, AAV1-Rheb(S16H) transduction in the hippocampus of transgenic AD mice prevented cognitive function impairment [26,29].…”
Section: Mutation Of Rheb Leading To Constitutive Activationmentioning
confidence: 90%
“…The mutation of serine to histidine at position 16 of Rheb [Rheb(S16H)] has been found to exhibit gain-of-function properties, resulting in highly activated mTOR signaling in TSC1/2-overexpressing cells [128]. Our previous studies showed that the overexpression of Rheb(S16H) could significantly increase the levels of NTFs such as GDNF, CNTF, and BDNF in the adult brain [5,11,26,29,69]. The mutation of tyrosine to asparagine at position 35 of Rheb [Rheb(Y35N)] in renal cell carcinoma has been reported to cause mTORC1 hyperactivation by increasing the resistance to TSC2 GAP activity, resulting in the hyperproliferation of tumor cells [129].…”
Section: Mutation Of Rheb Leading To Constitutive Activationmentioning
confidence: 99%
See 3 more Smart Citations